Micropropagation of cork oak (Quercus suber L.) by apical bud culture from embryonic axes - El Kbiach, M. L.; Lamarti, A.; Abdali, A.; Badoc, A. (ACTA BOTANICA GALLICA, 2004)
To improve the in vitro germination and development of cork Oakembryonic axes, several mineral media were tested; Durzan medium modified 1/2 supplemented with 400 mg/l glutamine and 3% sucrose gave the best results. The action of BA alone or combined with other growth regulators was also studied. A low concentration (0.44 mu M) was found to give an acceptable percentage of plantlets. When combined with NAA, callogenesis was observed. The transfer of cultures in conditions of low luminosity led to the formation of several axillary buds. These buds were multiplied on a solid medium supplemented with GA(3) at low concentration. The buds were elongated, then rooted on a growth regulator-free medium after brief dipping in an auxinic solution. The rooted plants were potted on horticultural substrate.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: cork oak; Quercus suber; in vitro culture; embryon